2010
DOI: 10.2337/dc09-1762
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Metabolic Syndrome and Other Baseline Factors and the Efficacy of Ezetimibe/Simvastatin and Atorvastatin in Patients With Type 2 Diabetes and Hypercholesterolemia

Abstract: OBJECTIVETo investigate relationships between baseline factors and treatment-associated efficacy changes in type 2 diabetes.RESEARCH DESIGN AND METHODSMultivariable analyses of treatment response in 1,229 type 2 diabetic patients with hypercholesterolemia who received ezetimibe/simvastatin or atorvastatin in a randomized double-blind 6-week study.RESULTSIncreasing age was related to improvements in all lipid assessments. Men had greater triglyceride and non-HDL cholesterol reductions than women, and black/Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…These were consistent with the expectations for the dyslipidaemia profiles in patients with diabetes and/or the MetS. Of note, greater lipid responses and/or target attainment were achieved with the combination of ezetimibe/simvastatin treatment regimen compared with statin monotherapy in all of the previous studies as well as the current analysis [14][15][16], supporting the premise that it may be necessary to use combination therapies or to intensify current statin therapy in patients with elevated cardiometabolic risk in order to achieve recommended treatment targets [6][7][8]. Whether these baseline differences impacted the magnitude of change in the lipids is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…These were consistent with the expectations for the dyslipidaemia profiles in patients with diabetes and/or the MetS. Of note, greater lipid responses and/or target attainment were achieved with the combination of ezetimibe/simvastatin treatment regimen compared with statin monotherapy in all of the previous studies as well as the current analysis [14][15][16], supporting the premise that it may be necessary to use combination therapies or to intensify current statin therapy in patients with elevated cardiometabolic risk in order to achieve recommended treatment targets [6][7][8]. Whether these baseline differences impacted the magnitude of change in the lipids is unknown.…”
Section: Discussionsupporting
confidence: 89%
“…Trials of common statins have shown reduced LDL-C response in AA vs. EA, resulting in diminished LDL-C control despite high adherence in all subgroups [48,49]. Specific genetic loci with interethnic frequency differences that are associated with variable drug response have been identified.…”
Section: Why Is There An Interethnic Difference?mentioning
confidence: 99%
“…At least one article describes some differences. 14 Other articles find no such differences. 15,16 In the present study, if the Hispanic population had been more likely to benefit from simvastatin administration, then a lower number of Hispanic patients in the treatment group could lead to type II error.…”
mentioning
confidence: 97%
“…15,16 In the present study, if the Hispanic population had been more likely to benefit from simvastatin administration, then a lower number of Hispanic patients in the treatment group could lead to type II error. However, work by Goldberg et al 14 indicates that Hispanic patients were actually less responsive to statins than other ethnic groups. Therefore, the scarce evidence available might actually bolster the author's findings.…”
mentioning
confidence: 99%